Effects of oceanic circulation and volcanic ash-fall on calcite dissolution in bathyal sediments of the last 550 ka (Chatham Rise; SW Pacific Ocean) - COBIANCHI, MIRIAM; MANCIN, NICOLETTA; LUPI, CLAUDIA; Bordiga M.; Hayward B. (2014)
The effects on calcite dissolution of both volcanic ash-fall and oceanic circulation were evaluated in lower bathyal sediments from the last 550 ka record of the core MD 97-2114, recovered on the northern slope of the Chatham Rise ( east of New Zealand, SW Pacific Ocean). This area was involved, during the Late Pleistocene, by the local activity of the Taupo Volcanic Zone and by the main changes of ocean chemistry and circulation following the end of the Mid-Pleistocene Transition. Several micropaleontological dissolution proxies, based on planktonic foraminifera and calcareous nannofossils (FI%, TFI%, NDI) were obtained by new analyses in order to evaluate the calcium carbonate dissolution on the deep-sea sediments. Geochemical and micropaleotological proxies of primary productivity (e.g. 13Cp–b and foraminiferal Epifauna/Infauna ratio) complete the dataset. The data collected from the studied core were then compared with those of the nearby deeper ODP 1123 and shallower 1125 sites, both located north of the Chatham Rise, in order to reconstruct the glacial-interglacial CaCO3 dissolution history , at different depths, during the last 550 ka. Results demonstrate that: (1) the CaCO3 dissolution/preservation cycles at the studied site show periodicities at G-I scale that match the Pacific-style CaCO3 cycles of Naidu and Malmgren (1999); (2) several short-term dissolution events do not follow this general scheme and some of them occur during tephra deposition; (3) the dissolution related to the tephra deposition seem to affect mostly calcareous nannofossils, thus we hypothesise that the reduction of the surface water pH (below 7.8) induced by the ash-fall influences above all the calcite precipitating organisms inhabited the more surficial ecological niches. On the contrary, the planktonic foraminifera seem to be mostly affected by dissolution within the water column and at the sea floor with respect to calcareous nannofossils which dissolve far more slowly than foraminifera for settling through fecal pellets. ...